2019
DOI: 10.3906/sag-1904-49
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parathyroidectomy on bone mineral density in primary hyperparathyroidism

Abstract: Background/aim: This study aimed to investigate the change in bone mineral density (BMD) before and 1 year after parathyroidectomy in patients with primary hyperparathyroidism (PHPT). Materials and methods: The clinical and biochemical parameters and DEXA screening of patients with symptomatic PHPT (n = 28) and asymptomatic PHPT (n = 63) were investigated before and 1 year after parathyroidectomy. Results: Patients with symptomatic PHPT had a higher prevalence of nephrolithiasis (18.2% vs. 4.6%, P = 0.032) whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Although our study failed to find a correlation between β-CTx at baseline and BMD changes after RFA, ALP correlated negatively with BMD in both the lumbar spine and femoral neck. There was a decrease of BMD in the lumbar spine of patients with PHPT, which is consistent with other series studies on PTX ( 5 , 16 - 18 , 22 ). Another principal finding was that RFA was associated with an increase in the BMD to the level of that of the age-matched controls in the lumbar spine but not in the femoral neck.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although our study failed to find a correlation between β-CTx at baseline and BMD changes after RFA, ALP correlated negatively with BMD in both the lumbar spine and femoral neck. There was a decrease of BMD in the lumbar spine of patients with PHPT, which is consistent with other series studies on PTX ( 5 , 16 - 18 , 22 ). Another principal finding was that RFA was associated with an increase in the BMD to the level of that of the age-matched controls in the lumbar spine but not in the femoral neck.…”
Section: Discussionsupporting
confidence: 92%
“…The beneficial effect of PTX on bone involvement has been demonstrated ( 16 - 20 ). In our cohort, as many as 81% of the cases had a low BMD at the lumbar spine or femoral neck compared with 29% of the matched controls, which suggests significant bone loss in patients with mild PHPT.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term postoperative follow-up analysis of BMD in patients with hyperparathyroidism is limited in the literature. 13 The present study assessed patients with moderate to severe PHPT for 2 years following surgery. We observed that BMD of the total hip and lumbar spine was significantly improved after 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies focused on primary hyperthyroidism and did not distinguish patients with the severe form of this disease. 13 , 14 The present study performed a comprehensive analysis of patients with moderate to severe PHPT in our hospital. BMD measurements were performed using dual-energy X-ray absorptiometry (DXA) to analyze changes in BMD at different sites, including the lumbar spine and total hip, before parathyroidectomy, and 6 months, 1 year, and 2 years after parathyroidectomy.…”
Section: Introductionmentioning
confidence: 99%